Evaluation of CAG repeat length in the androgen receptor gene and polycystic ovary syndrome risk in Iranian women: A case-control study - Hamideh Arasteh; Fatemeh Araste; Mohammad Hasan Sheikhha; Ph.D; Seyyed Mehdi Kalantar; Ehsan Farashahi Yazd; Hamid Reza Ashrafzadeh; Nasrin Ghasemi (Shahid Sadoughi University of Medical Sciences, 2022)
Abstract Background: Polycystic ovary syndrome (PCOS) is a heterogeneous disorder, which affects about 15-20% of women of reproductive age. The most important etiopathogenesis factor in its incidence is hyperandrogenism; over 70 candidate genes are known to be associated with this syndrome, such as the androgen receptor (AR) gene which encodes a steroid receptor and is located on the Xq11-12 chromosome. The N-terminus of exon 1 of AR contains a polymorphic trinucleotide repeat (CAG)n region that encodes glutamine tract. There are some studies showing that shorter AR CAG repeats are significantly related to enhanced AR sensitivity. Objective: This study investigated the frequency of the polymorphic expansion of the trinucleotide CAG repeats of AR in PCOS. Materials and Methods: 160 Iranian women aged 17-40 yr participated in this case-control study: 80 women as PCOS patients and 80 women as healthy controls according to the Rotterdam criteria. Other similar phenotype factors such as hyperandrogenism were not considered as PCOS. The frequency of polymorphic expansion of CAG trinucleotide repeats in PCOS patients was compared with the frequency in non-PCOS controls in using two primer sets for nested polymerase chain reaction. The polymerase chain reaction products were visualized on polyacrylamide gel and then were confirmed by a sequencing process. Results: The results did not show a significant correlation between the frequency of CAG repeats in AR and PCOS incidence. Conclusion: In contrast to some previous reports, the present data showed that the CAG length in PCOS cases did not significantly differ from that of controls. So, the AR (CAG)n does not appear to be a major factor for PCOS in Iranian women.